Beispiel Nr: 04
$ \text{Gegeben:}\\\text{Umfang} \qquad U \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{U - 2\cdot a}{ 2}\\ \textbf{Gegeben:} \\ U=60m \qquad a=5m \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{U - 2\cdot a}{ 2} \\ U=60m\\ a=5m\\ b = \frac{60m - 2\cdot 5m}{ 2}\\\\b=25m \\ \small \begin{array}{|l|} \hline a=\\ \hline 5 m \\ \hline 50 dm \\ \hline 500 cm \\ \hline 5\cdot 10^{3} mm \\ \hline 5\cdot 10^{6} \mu m \\ \hline 0,005 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline U=\\ \hline 60 m \\ \hline 600 dm \\ \hline 6\cdot 10^{3} cm \\ \hline 6\cdot 10^{4} mm \\ \hline 6\cdot 10^{7} \mu m \\ \hline 0,06 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 25 m \\ \hline 250 dm \\ \hline 2,5\cdot 10^{3} cm \\ \hline 2,5\cdot 10^{4} mm \\ \hline 2,5\cdot 10^{7} \mu m \\ \hline 0,025 km \\ \hline \end{array}\\$